Temporal and Spatial Change Monitoring of Drought Grade Based on ERA5 Analysis Data and BFAST Method in the Belt and Road Area during 1989–2017 - Changdi Xue; Hua Wu; Xiaoguang Jiang (Advances in Meteorology)
Drought is a worldwide natural disaster with a wide range of influences and a long duration, which has a huge impact on the agricultural production activities and social economy of local residents. The Belt and Road Initiative has always received much attention due to its special geographical location and great potential for economic development. At the same time, the Belt and Road region is also deeply affected by drought, especially in some countries and regions, where the agricultural infrastructure is weak and the ecological environment is fragile. How to effectively monitor and evaluate drought has become an urgent problem to be solved. In this study, the ERA5 atmospheric reanalysis data were used, and the self-calibrating Palmer Drought Severity Index was combined with Breaks for Additive Seasonal and Trend (BFAST) to study the temporal and spatial distribution of the 1989–2017 monthly scale of drought in different climate regions of the Belt and Road region. The results show that the overall change trend of arid area shows a change of “up-down-up-down.” The winter drought area is larger than the summer drought area, and the drought center gradually moves from the Southeast Asia region in winter to the West–Central Asia region in summer. In the past five years, the drought area decreased gradually at the rate of approximately 0.38 million km2 per year.